2017
DOI: 10.1016/j.ijmedinf.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the benefits and challenges of health professionals’ participation in online health communities: Emergence of (dis)empowerment processes and outcomes

Abstract: This small study demonstrates that health professional participating in OHCs as moderators perceive themselves as facilitators of patients and other OHC's users empowering processes and outcomes, in which OHC's users improve their health literacy, develop skills, expand their social support, and gain other important resources necessary when dealing with health-related issues. Health professional moderator's role, however, also involves several duties, responsibilities and limitations that are often experienced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 35 publications
4
56
2
2
Order By: Relevance
“…Overall, our analysis reveals some patterns of WOM on online health consultation: (1) From the results of the descriptive analysis, we can conclude that the IT-Enabled health service is experiencing an increased tendency as confirmed in other research [43]. (2) The results of the term frequency analysis show that while patients' concerns on IT-Enabled health service vary from doctors, website function, emotional support and the physician-patient relationship, the emphasis lies in service quality and benefit acquisition.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Overall, our analysis reveals some patterns of WOM on online health consultation: (1) From the results of the descriptive analysis, we can conclude that the IT-Enabled health service is experiencing an increased tendency as confirmed in other research [43]. (2) The results of the term frequency analysis show that while patients' concerns on IT-Enabled health service vary from doctors, website function, emotional support and the physician-patient relationship, the emphasis lies in service quality and benefit acquisition.…”
Section: Discussionsupporting
confidence: 68%
“…Those websites utilize interactive communication and information technology to bridge the gap between healthcare consumers and caregivers. Through enhancing the physician-patient relationship and providing access to valued resources that can be shared among members, they advocate the information and service collaboration among health professionals, researchers, patients, and their family members, with the goal of tackling health issues [2]. To date, there have been a large number of studies and systematic literature reviews on IT-Enabled collaboration in healthcare context, ranging from the design of health information systems [6] to the implementation of HIT [36].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in other community-based projects participants actively contribute their skills, knowledge, and time. [16] suggest that the main reasons doctor volunteer in a HVCs include altruism, knowledge sharing and for career enhancement opportunities. Other factors include opportunity to enhance their professional networks, access valuable knowledge and improve clinical practice [26].…”
Section: Literature Reviewsmentioning
confidence: 99%
“…A study by [16] reported that doctor's responsibilities and constraint related to their job has been a problem for them in providing patient in HVCs better online medical services. Furthermore, 19% of major HVCs moderated by doctors showing potential limitations in time [17].…”
Section: Introductionmentioning
confidence: 99%
“…The Information Systems professionals have been interested in the technologies that enable online communities, and they have produced a rich literature on users' participation in online communities. The success of an online health community depends on the members' loyalty in terms of continuing participation [7][8][9]; in other words, an online community will not survive without lasting user motivation and participation [10][11][12]. As such, it is necessary to understand the people who will use the service, the goals or tasks they have, and their context of use [13].…”
Section: Literature Reviewmentioning
confidence: 99%